(untitled) (AYUSHDHARA, 2022)
Hypothyroidism in one among the lifestyle and metabolic disorders having great prevalence in the world wide. It occurs when the thyroid gland is not making enough hormones for good health. It effects multiple organ system so the symptoms of hypothyroidism are wide ranging and diverse. In spite of many advance techniques the allopathic management of hypothyroidism still remains unsatisfactory. Ayurveda is holistic approach particularly Panchakarma which aims at eliminating the Doshas from its root. Hence Vamana karma is found to be effective treatment in hypothyroidism due to involvement of abundant Kapha dosha with Pittanubandha and also involvement of Rasavaha, Medovaha dushti and Bahudoshavastha lakshnas. Hence in this present of 6 patients where Vamana Karma is conducted in Vasanta ritu. There was significant decrease in thyroid stimulating hormone (TSH) level and marked improvement in signs and symptoms.